2013
DOI: 10.1016/j.cub.2013.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Influences on Auditory Streaming

Abstract: SummaryBiologically salient sounds, including speech, are rarely heard in isolation. Our brains must therefore organize the input arising from multiple sources into separate “streams” and, in the case of speech, map the acoustic components of the target signal onto meaning. These auditory and linguistic processes have traditionally been considered to occur sequentially and are typically studied independently [1, 2]. However, evidence that streaming is modified or reset by attention [3], and that lexical knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 25 publications
4
62
0
Order By: Relevance
“…These circumstances typically lead to even more degraded and ambiguous acoustic cues to a spoken message than occur for speech in quiet, owing to energetic and informational masking between voices. The results of the study reported here are in accord with the notion that a comprehensive account of spoken word recognition must involve reciprocal interactions between auditory stream segregation and linguistic knowledge, whereby each affects the other (Billig et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These circumstances typically lead to even more degraded and ambiguous acoustic cues to a spoken message than occur for speech in quiet, owing to energetic and informational masking between voices. The results of the study reported here are in accord with the notion that a comprehensive account of spoken word recognition must involve reciprocal interactions between auditory stream segregation and linguistic knowledge, whereby each affects the other (Billig et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…For general auditory grouping, these factors include attention and switching attention (e.g., Cusack et al, 2004), and the effects of pattern regularity on stream formation and stabilization (e.g., Bendixen et al, 2010;Devergie et al, 2010). For the perceptual organization of speech, additional factors include articulatory constraints (e.g., Basirat et al, 2012) and lexical constraints (e.g., Billig et al, 2013). Listening to speech in the presence of other speech is commonplace and doing so involves concurrent segregation, as in the VTE study reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In partial support of this idea, a recent study with sentences involving cochlear implant listeners (Bhargava et al, 2014), extending the study of Miller and Licklider (1950), showed that in some cases strong continuity illusion could be observed without a phonemic restoration effect and that in other cases better phonemic restoration benefit could be observed with lesser continuity illusion. To explain our persistent phonemic restoration effect, we propose that the participants were able to focus on the message, and that the high linguistic context of the sentences enabled participants to overcome the voice discontinuity to create a higher-level reconstructed representation (also supported by Billig et al, 2013;Warren and Sherman, 1974). This implies that, at this slow rate of interruptions, participants would rely on the linguistic context to achieve phonemic restoration and would not be disturbed by the inconsistent indexical cues.…”
Section: Discussionmentioning
confidence: 86%
“…This perceptual organization is referred to as streaming (Carlyon 2004;Bregman 1990). Auditory streaming is a basic capacity of the auditory system and is influenced by the acoustic cues of the stimulus as well as by higher-level semantic processes (Billig et al 2013). Whereas frequency and timbre are some of the most powerful acoustic cues used for auditory streaming (for reviews see e. g. Darwin 1999;Carlyon 2004;Moore and Gockel 2012), spatial cues can play an important role in auditory stream segregation as well.…”
Section: The Interaction Between Semantic and Spatial Information -Evmentioning
confidence: 99%